2002
DOI: 10.1098/rspb.2002.2195
|View full text |Cite
|
Sign up to set email alerts
|

Scaling in stream communities

Abstract: Scaling relationships between population density (N) and body size (W ), and of their underlying size distributions, can contribute to an understanding of how species use resources as a function of size. In an attempt to resolve the controversy over the form of scaling relationships, an extensive dataset, comprising 602 invertebrate species, was obtained from two geographically separate stream communities (Seebach in Austria and Mynach in Wales). We analysed the temporal consistency of the N-W relationship, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 26 publications
2
24
0
3
Order By: Relevance
“…Fractal methods have been used to describe textural differences in constructed substrates with a checkerboard arrangement of heights (Taniguchi & Tokeshi, 2004), estimate the fractal dimension of riverbed topography (Robson et al, 2002), and describe the substrate-water interface of streambeds (Schmid et al, 2002). Fractal geometry has also been used in marine benthic studies (e.g.…”
Section: Overview Of Methods For Measuring Roughnessmentioning
confidence: 99%
“…Fractal methods have been used to describe textural differences in constructed substrates with a checkerboard arrangement of heights (Taniguchi & Tokeshi, 2004), estimate the fractal dimension of riverbed topography (Robson et al, 2002), and describe the substrate-water interface of streambeds (Schmid et al, 2002). Fractal geometry has also been used in marine benthic studies (e.g.…”
Section: Overview Of Methods For Measuring Roughnessmentioning
confidence: 99%
“…In benthic environments, however, organisms can find refuge among the fronds of macroalgae or in sediment interstices, and therefore, environmental factors such as habitat architecture and substrate composition strongly affect the size structure of benthic communities (Strayer 1991;Holling 1992;Schmid 2000;Tokeshi and Arakaki 2012). In fact, the availability of shelters of different dimensions influences the size of crabs (Beck 1995), and different morphologies of macroalgae as well as different levels of habitat complexity determine the size spectra of amphipods (Hacker and Steneck 1990), gastropods (Pennings 1990), epifaunal (Gee and Warwick 1994) and infaunal assemblages (Schmid et al 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Aquatic ecologists, for example, have usually analyzed the frequency distribution of body sizes regardless the species to which organisms belong, or body size spectra, and studies conducted in small water bodies have reported scaling exponents that largely deviate from the expected value of -3/4 (Boix, Sala, Quintana, & Moreno-Amich, 2004;Schmid, Tokeshi, & Schmid-Araya, 2000, 2002. Indeed, recent studies on benthic macroinvertebrates from Mediterranean lagoons have shown that local body size-abundance relationships can be polygonal in shape, with the highest population density per size class increasing with average individual body size of 0.25 mg and decreasing beyond this threshold (Barbone, Rosati, Pinna, & Basset, 2007;Basset et al, 2008).…”
mentioning
confidence: 99%